PERILAKU MENABUNG MASYARAKAT DITINJAU DARI INKLUSI KEUANGAN, PRODUK TABUNGAN DAN PELAYANAN (Studi Kasus di PT. BPR Guna Daya Boyolali) - Anis Dhanikafuri; Sudarwati Sudarwati; Fithri Setya Marwati (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study is to analyze the simultaneous or partial influence of financial inclusion, savings products and services at PT. BPR For Boyolali Power. This type of research is quantitative descriptive. The population of this study are people who are customers of PT. BPR Guna Daya (856). The sample consisted of 100 respondents. Data obtained by conducting a questionnaire with accidental sampling techniques. The data analysis technique used is multiple linear regression analysis. F test results prove that financial inclusion, savings products and services simultaneously affect the behavior of people saving at PT. BPR For Power, where the value of F count = 26.292> Ftable = 2.70 with a significance value of 0.000 1.660 and significant 0.025